Síntese de glicodendrímeros e sua aplicação como nanoreatores - Menger, Renata (2020)
Nanoparticles stabilized by dendrimers have been widely used in the field of catalysis due to their nanometric size, uniform dispersion and good stability. Dendrimers have advantages compared to conventional polymers due to the high symmetry in their structure and organization of the molecule in space, in addition to presenting terminal groups that can be modified for various applications. In this work, the PAMAM dendrimer (poly (amidoamine)) until the fourth generation, PG4-NH2, was synthesized, with amine groups as surface groups. The synthesis of glycodendrimers was carried out via a reductive amination reaction from the dendrimer PAMAM with the oligosaccharides lactose and maltodextrin. The glycosylated dendritic derivatives, PG4-MDX and PG4-LAC, as well as PG4-NH2 were used in the stabilization of silver nanoparticles and tested as catalysts in the reduction of p-nitrophenol (4-Nip) in p-aminophenol by NaBH4. The three nanocatalyst systems were studied at temperatures of 15, 20 and 25 °C. From the kinetic curves obtained for the catalytic reduction reaction, the apparent reaction speed constant values (kapp) were obtained and the efficiency of the nanocatalyst was calculated from the TOF (turnover frequency) with the data of the initial concentration of 4-Nip divided by the silver concentration multiplied by the time elapsed in the reduction reaction. The highest kapp and TOF values were obtained for reactions carried out at 25 °C. For Ag-NPs formed by PG4-NH2, kapp = 0.0148 s-1 and TOF = 10100 h-1 were obtained, with the best result found followed by PG4-MDX with kapp values = 0.0144 s-1 and TOF = 877 h-1 and PG4-LAC with kapp = 0.0095 s-1 and TOF = 714 h-1. The results of kapp and TOF were compared with systems derived from the PAMAM G4 dendrimer presented in the literature and the nanocatalysts obtained in this work showed higher values for the kapp and higher or similar catalytic efficiency to the other systems. For PG4-NH2 the kapp value was 4 times greater and 2.7 times greater the catalytic efficiency compared to the same nanocatalyst published by Yang and collaborators.